Dumping and Anti-dumping actions - Mavila Hinojoza, Daniel (2010)
The Dumping is the practice of trade in which a company sells a product abroad at less than that would be sold in its home market. The present article describes the steps that should follow either a company or a branch of production, that might be affected by dumping prices.